Embodiment, relation, community : a continental philosophy of communication - Butchart, Garnet (The Pennsylvania State University Press, 2019)
"Integrates the perspectives of Giorgio Agamben, Roberto Esposito, Jean-Luc Nancy, and Lacanian psychoanalysis to distinguish communication theory from the philosophy of communication"--Provided by publisher